Comercialização de filmes independentes e o caso 3 efes - Melo, Maria Cristina Couto (Universidade Federal de São Carlos, 2014)
The industrial model of filmmaking is structured by dividing the production of a film between three sectors. Production, distribution and exhibition, and the gradual and sequential content offer in the viewports. The distribution and exhibition sectors are responsible for the film commercialization, both work together in order to enable commercial success of production and monetize their own activities. Currently, the distribution activity is exercised by American conglomerates of media, the majors, and by independent distributors that operate on a national scale, usually with smaller films, called niche films. However, the development of new media and the communication media's convergence resulted in a model that proposes the content display on multiple windows and production by niche's demand . This research proposes to discuss and understand the role of the new display windows, potentiated by the convergence of media vehicles, as diffusion of alternative independent audiovisual productions. As an example, it will be discussed the distribution strategy for the movie 3 Efes (Carlos Gerbase, 2007).
Keywords: Cinema independente; Cinema - distribuição; Filme de nicho; 3 Efes; Film distribution; Niche film; Independent; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA